Persepsi dan Partisipasi Ketua Dewan Kemakmuran Masjid (DKM) Di Kelurahan Cipadung Kidul Kecamatan Panyileukan Kota Bandung Terhadap Kredit Mesra - Nandang Ihwanudin; M. Burhanudin (STAI Siliwangi Bandung, 2020)
This research is motivated by the Bandung City Government's policy of rolling out the Prosperous Mosque Credit Program (Mesra), which is a loan program without collateral and without interest. This policy is intended to move the economy, improve the welfare of the community, minimize the practice of moneylenders who are troubling the community, and foster new entrepreneurs. This program is an embodiment of the idea to make a mosque not only a place of worship but also a center of community economic growth. Practically in the field, from the results of the preliminary study, two of the four board members of DKM did not yet know about MESRA credit program. While other managers know about MESRA credit program, but do not know how it is implemented. Therefore, the authors are interested in conducting research on the perceptions and participation of the board of the Mosque Prosperity Council (DKM) on the MESRA Credit Program in the City of Bandung. This research uses descriptive analysis method, the type of data is information; and data sources can be obtained by researchers through primary data in the form of interviews with DKM management and secondary data in the form of various journals, research articles, and books, websites, etc. which are all closely related to understanding and perception, as well as the participation of DKM administrators towards the MESRA Credit program in the City of Bandung. The results of this study concluded that the understanding from management of DKM about the MESRA Credit Program in Bandung was still very low and there was no participation from them in succeeding the program. Next, the authors suggest to the stakeholders to conduct massive socialization to the public and to the board of the DKM and mobilize related elements such as Ministry of Religion, BAZDA, MUI, and related financial institutions.